Influence of Formazan Derivatives on Corrosion Inhibition of Mild Steel in Hydrochloric Acid Medium. Issue Volume 6:Issue S1(2009) (2009) - Venkatesan, P.; Anand, B.; Matheswaran, P.
Abstract : Formazan of benzaldehyde (FB) and formazan of p -dimethyl amino benzaldehyde (FD) were synthesized. These compounds were studied as corrosion inhibitor for mild steel in 1.11 N hydrochloric acid by weight loss method. The result showed that the corrosion inhibition efficiency of these compounds was found to vary with the temperature and acid concentration. Also, it was found that the corrosion inhibition behaviour of FD is greater than that of FB. The kinetic treatment of the results gave first order kinetics. The relative corrosion inhibition efficiency of these compounds has been explained on the basis of structure dependent - electron donor properties of the inhibitors.